Evaluation of T cell recognition of theileria parva homologs of apicomplexan antigens. - Kangethe, R.T. (University of Nairobi, 2007)
East Coast fever is a severe lymphoproliferative disease of cattle caused by the intracellular protozoan Theileriaparva from the family Apicomplexa, CD8+ cytotoxic T lymphocyte (CTL) mediated destruction of parasite infected lymphocytes constitutes the dominant protective immune response following exposure to infection or vaccination using a live infection and treatment protocol. Appropriate delivery of parasite antigens targeted by CTL from T parva immune cattle has long been proposed as a strategy for the development of a subunit vaccine that would contribute substantially to a sustainable integrated ECF control program. Gene homologs encoding antigens from other apicomplexan parasites constitute a source of vaccine candidate antigens. The aim of this study was to evaluate the recognition of T parva homologs of known apicomplexan antigens by CD8+ and CD4+ T lymphocytes isolated from cattle immunized by a live vaccine. Eight T parva homo logs of apicomplexan antigens were sub-cloned into a eukaryotic expression vector and transiently transfected into bovine antigen presenting cells (APC). Recognition of transfected APC by T parva specific CD8+ CTL lines was assessed using an IFN-y ELISpot assay but none of the 7 CTL lines tested recognized any of the homologs. A recombinant protein was generated representing atruncated version of one T parva protein designated X9-3 (a homolog of T Complex Protein-I zeta subunit in Babesia microti) and tested in immunoassays for recognition by T cells from immune cattle. Peripheral blood mononuclear cells from 3112cattle and a T parva specific polyclonal CD4+ T cell line from immune cattle BW014 responded to the X9-3 protein. The results suggest that none of the eight homolog genes are CTL target antigens but X9-3 is a candidate T-helper cell target antigen and should be considered for inclusion in a subunit vaccine against ECF